PERUBAHAN POLA SENI TRADISIONAL TAYUBAN DI MADIUN - Ilmiyatus Syahro (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: The research objective of this article is to find out changes in the pattern of Taruban art in Madiun. This research focuses on 1. What is the History of the Community's Tayuban Tradition in East Java. 2. How is the Implementation of the Community Tayuban Tradition Event in Purwosari Village. 3. What is the Meaning of Philosophy and the Influence of the Tayuban tradition. The approach and theoretical framework used in this study is the historical and cultural anthropological approach, for the theory using Clifford Geertz on interpretive culture. While the research method used is the method of cultural anthropology with field observations and interviews conducted directly, researchers also participate in the implementation of these traditions. From the results of this study it can be concluded that the existence of the Tayub tradition has been known since the Hindu and Buddhist eras, seen from the reliefs found in the temples in Central Java. In Serat Centhini, the art of Tayub emerged in the 19th century. The procedure for carrying out the Tayuban tradition in Purwosari village is still the same as before, but for now, yasin and tahlil readings are being held. While significant changes have occurred in its noble values ​​which have shifted from time to time, namely from Hindu noble values ​​to Islam. Keywords: change, art, traditional, Madiun